Tatanan Sosial Islami - Nur Cahyo, Eko (Literasi: Jurnal Ilmu Pendidikan, 2009)
In the book "Theory and Practice of Islamic Economics: The Basics of Islamic Economics" Dr. Mohammad Abdul Mannan, explained that the Islamic social order is based on the Quran and the Sunnah of the Prophet Muhammad, which can be formed if each resident is able to maintain harmony among the families, families with the public, community and government, namely creation of an implementation of the rights and obligations can be met. Furthermore, he expressed the characteristics of an Islamic social order that is social equality, the right to exploit the wealth proportionately and private ownership recognized and protected in Islam, an Islamic mandate to engage in economic activities by setting a good rule to ensure the implementation of these activitiesin an honest and benefit, elimination of the capitalist system in all fields of economic activity,  modern planning concept that refers to the utilization of domestic resources to achieve certain goals which are subject to the orders of the holy book of Qur'an and Sunnah, the creation of social justice. Other than that he would affirm the concept of welfare state in Islam, by applying the values in the teachings of Islam as a moral and spiritual values,  economic values, and Islamic social and political values.  Next will be explained about the Islamic social order is clear, concise, and solid.Keywords: Islamic social order and its characteristics, the concept of welfare states with moral , spiritual, social, political, and economic.